Association of prostate zonal volume with location and aggressiveness of clinically significant prostate cancer: A multiparametric MRI study according to PI-RADS version 2.1. Issue 150 (May 2022) - Yang, Ling; Li, Mou; Zhang, Meng-Ni; Yao, Jin; Song, Bin
Highlights: A large-scale analysis of the performance of 3.0 T mpMRI and PI-RADS v2.1 was conducted to investigate the relationship between prostatic zonal volume and carcinogenesis and aggressiveness of PCa. Prostate cancer (PCa) with high GS is more likely to have a relatively larger peripheral zone and involve the PZ, while PCa with a larger transition zone is more likely to have a low GS. This study support the theoretical model that pressure exerted by increasing prostate size/mechanical deformation may inhibit PCa growth. Abstract: Background: The relationship between prostate cancer (PCa) and benign prostatic hyperplasia (BPH) remains unclear. This study aimed to determine whether prostate zonal volume was associated with the location and aggressiveness of PCa. Methods: 412 PCa patients were retrospectively enrolled. The volumes of the whole prostate (V) and transition zone (Vtz) were calculated by the prolate ellipsoid formula, and volume of the peripheral zone (Vpz) was calculated by their subtraction. Locations of PCa were divided into three categories, including peripheral zone (PZ), transition zone (Vtz) and mixed zone group. The mixed zone group was further divided into PZ-dominated, TZ-dominated and equally distributed subgroups. Results: The Vtz of Gleason score (GS) 3 + 4 group was the largest, while the Vpz of GS 9 group was the largest. Tumor diameters of the PZ and TZ groups were weakly correlated with their corresponding zonal volume (r = 0.261, p < 0.001; r = 0.311, p = 0.009, respectively). There was no significant difference in the zonal volumes and GS distribution among the location groups. The proportion of tumors with high-grade GS of 8 and 9 was higher in the PZ than that in the TZ group (38.5 vs 24.3%, p = 0.041). For tumors located in the TZ, the V and Vpz of tumors with high-grade GS were larger than those in the low-grade GS of 7 group ( p = 0.033 and 0.039, respectively). Among the subgroups of mixed zone group, the Vtz of the TZ-dominated group was larger than those of PZ-dominated and equally distributed groups ( p = 0.016 and 0.001, respectively). Conclusion: PCa with high-grade GS is more likely to have a relatively larger Vpz and involve PZ, while PCa with a larger Vtz is more likely to be with low-grade GS, which support the theoretical model that pressure exerted by increasing prostate size/mechanical deformation may inhibit PCa growth from the clinical point. However, the increase in zonal volume might not be the direct cause of tumorigenesis and aggressiveness.